ChemInform Abstract: Metal‐Free One‐Pot Synthesis of Benzofurans. Issue 1 (January 2015) - Ghosh, Raju; Stridfeldt, Elin; Olofsson, Berit
Abstract The arylation of acetohydroxamate with diaryliodonium salts yields O‐arylated products.